Electron-impact dissociation of molecular hydrogen into neutral fragments - Scarlett, L.; Tapley, J.; Fursa, Dmitry; Zammit, M.; Savage, J.; Bray, Igor (Springer, 2018)
© 2018, EDP Sciences, SIF, Springer-Verlag GmbH Germany, part of Springer Nature. Abstract: We present convergent close-coupling calculations of electron-impact dissociation of the ground state of molecular hydrogen into neutral fragments over the range of impact energies from 6 to 300 eV. The calculations account for dissociative excitation, excitation radiative decay dissociation, and predissociation through all bound electronic triplet states, and singlet states up to the D' 1 ? u state. An estimate is given for the contribution from the remaining bound electronic singlet states. Our results are in agreement with the recommended data of Yoon et al. [J. Phys. Chem. Ref. Data 37, 913 (2008)] in the low (6–12 eV) and high (60–70 eV) energy regions, but somewhat lower at the intermediate energies. Graphical abstract: [Figure not available: see fulltext.] .